The Role of Islamic Education Teachers in Enhancing Students' Spiritual Intelligence: A Phenomenological Study - Munasir Munasir; Muhammad Zaki Akbar Hasan; Muchamad Rifki; Muhammad Januaripin (Khazanah Pendidikan Islam, 2026)
In the era of globalization and rapid technological advancement, students are increasingly exposed to complex challenges that affect their personal, social, and academic development. A competitive educational environment, unrestricted access to information, and dynamic social interactions require students to develop not only cognitive and emotional intelligence, but also spiritual intelligence that provides meaning, values, and moral direction in their lives. Spiritual intelligence plays a crucial role in helping students navigate ethical dilemmas, manage inner conflicts, and develop a sense of purpose. However, previous studies indicate that contemporary education tends to prioritize intellectual achievement and academic performance. Learning processes are often dominated by cognitive demands such as memorization, conceptual understanding, and test-oriented outcomes, while the internalization of spiritual and moral values receives relatively limited attention. As a result, students may achieve academic success but exhibit weaknesses in spiritual awareness, moral sensitivity, and self-regulation. This condition highlights a gap between educational goals and the holistic development of students, particularly in the spiritual dimension. In this context, the role of Islamic Education (PAI) teachers becomes highly significant. Although earlier research has emphasized the contribution of religious education to character formation, many studies focus mainly on curriculum or learning outcomes rather than students’ lived experiences. Therefore, this study employs a qualitative approach with phenomenological methods to explore how students perceive and experience the role of PAI teachers in enhancing spiritual intelligence. The findings reveal that PAI teachers function as spiritual role models, facilitators of religious activities, and spiritual mentors. At SMAN 1 Pamanukan, spiritual development is strengthened through religious habituation, Islamic school culture, student involvement in charitable activities and ROHIS, and reflective use of Islamic holidays and moments of calamity.